2006
DOI: 10.1191/0960327106ht589oa
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of saffron (Crocus sativus L.) aqueous extract against genetic damage induced by anti-tumor agents in mice

Abstract: The genotoxic potential of anti-tumor drugs limits their efficacy in the treatment of cancers. Since ancient times, saffron (dried stigmas of Crocus sativus L.) has been used as a spice and medicinal herb. Saffron is a rich source of carotenoids and is known for its anti-cancer and antitumor properties. The present study was designed to ascertain the chemoprotective potential of saffron against the genotoxicity of three well-known anti-tumor drugs-cisplatin (CIS), cyclophosphamide (CPH) and mitomycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 28 publications
2
51
0
4
Order By: Relevance
“…It has been reported that saffron or its ingredients such as crocin and dimethylcrocin are not mutagenic or genotoxic (Salomi et al, 1991a;Abdullaev et al, 2002Abdullaev et al, , 2003. Premkumar et al also showed that saffron aqueous extract protects from genotoxicity as well as genotoxins-induced oxidative stress in mice (Premkumar et al, 2001(Premkumar et al, , 2003(Premkumar et al, , 2006. In these studies, oral pretreatment with aqueous saffron extract (20, 40, and 80 mg=Kg) for 5 consecutive days significantly inhibited the genotoxicity of antitumor drugs (cyclophosphamide, mitomycin C, and cisplatin), in vivo, as revealed by micronucleus and comet assay.…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 96%
See 1 more Smart Citation
“…It has been reported that saffron or its ingredients such as crocin and dimethylcrocin are not mutagenic or genotoxic (Salomi et al, 1991a;Abdullaev et al, 2002Abdullaev et al, , 2003. Premkumar et al also showed that saffron aqueous extract protects from genotoxicity as well as genotoxins-induced oxidative stress in mice (Premkumar et al, 2001(Premkumar et al, , 2003(Premkumar et al, , 2006. In these studies, oral pretreatment with aqueous saffron extract (20, 40, and 80 mg=Kg) for 5 consecutive days significantly inhibited the genotoxicity of antitumor drugs (cyclophosphamide, mitomycin C, and cisplatin), in vivo, as revealed by micronucleus and comet assay.…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 96%
“…In these studies, oral pretreatment with aqueous saffron extract (20, 40, and 80 mg=Kg) for 5 consecutive days significantly inhibited the genotoxicity of antitumor drugs (cyclophosphamide, mitomycin C, and cisplatin), in vivo, as revealed by micronucleus and comet assay. It was suggested that saffron could exert its antigenotoxic and chemopreventive effects by the modulation of antioxidants and=or detoxification systems (Premkumar et al, 2001(Premkumar et al, , 2006. It was also reported that crocetin could significantly inhibit the genotoxic effects and neoplastic transformations of C3H1OT1=2 cells by benzo(a)pyrene (Chang et al, 1996).…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 99%
“…Chemical constituents and bioactivities of the liposoluble fraction from different medicinal parts of Crocus sativus chemopreventive potential against cancer (Abdullaev and Frenkel, 1992a,b;Escribano et al, 1996;Abdullaev and Espinosa-Aguirre 2004;Premkumar et al, 2006;Chryssanthi et al, 2007;Tavakkol-Afshari et al, 2008). Furthermore, antioxidant activity of saffron stigma and its active constituents were frequently reported (Nair et al, 1991;Assimopoulou et al, 2005;Naghizadeh et al, 2008).…”
Section: Research Articlementioning
confidence: 99%
“…This compound is cytotoxic against human cervical epithelioid carcinoma cells (IC 50 =7 mg/ml), and consists of approximately 90% carbohydrate and 10% protein. [63][64][65] …”
Section: Crocus Sativusmentioning
confidence: 99%